Scaffolding young Australian women's journey to motherhood: a narrative understanding. (6th April 2014) - Brand, Gabrielle; Morrison, Paul; Down, Barry; WestBrook, Be
Abstract Pregnant and young mothers' stories often go untold within community social and health service policy, planning and practice. Consequently, there is a significant gap between young women's experiences of motherhood and current service provision. This study was undertaken in response to a paucity of observational and contextually rich research that explores young women's experiences of pregnancy and motherhood, including the role a community service played in scaffolding their motherhood journeys. Fundamental to this study's purpose was the premise that to improve planning and delivery of more appropriate services for this group, we need to listen, consult and consider what life is like for young mothers. The purpose of this paper is to describe the role a community service played in scaffolding young women's experiences as they transitioned to motherhood. Using a narrative approach, this study draws on data collected from contextual observations of 31 informants and 11 in‐depth interviews over 7 months of fieldwork in 2010 at a community service in the Peel region of Western Australia. The integral role a community service played in the young women's transition to motherhood was analysed thematically and captured in three metaphorical themes, finding a circle of friends, weaving a tapestry and turning the page. The young women's storied experiences of motherhood present a strong argument for radical re‐visioning of community and social health policy, practice and service delivery for young mothers. The findings revealed that judgement‐free services that foster social and supportive relationships were integral in developing positive motherhood identities. The power of narrative and social learning when working with young mothers suggests that social models of health that foster a relational, narrative approach to practice are fundamental to young mothers finding their own voices and solutions and becoming active agents in re‐authoring future narratives of hope, autonomy and agency.